Analisis Ijtihad Syekh Yusuf Al-Qaradhawi Tentang Haramnya Talak Mu’allaq Perspektif Saddu Al-Dzari’ah - Bumulo, Zulkifli; Azwar, Zainal (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2025)
Sheikh Yusuf al-Qaradhawi is a contemporary scholar who is famous for his broad scientific insight, jurisprudence, and many works. He is among several scholars who are often asked for fatwas, one of his fatwas is regarding the prohibition of mu’allaq divorce (divorce that is dependent on certain conditions). This study analyzes the views of Sheikh Yusuf al-Qaradhawi regarding the law of mu’allaq divorce (conditional divorce) from the perspective of saddu al-Dzari'ah. With a normative qualitative approach based on literature study, it is found that he forbids and considers mu’allaq divorce invalid because it is not in accordance with Sharia. Al-Qaradhawi emphasizes that divorce must be done firmly and clearly, not in the form of conditions or oaths, because it can cause legal uncertainty and harm to the wife. This ijtihad analysis is based on the principle of saddu al-dzari'ah (closing the path to damage). With the perspective of saddu al-Dzari'ah, it can be concluded that mu’allaq divorce and swearing by divorce is forbidden and invalid, as a preventive measure against potential damage that will occur.